Produção, concentração e caracterização de cutinase - Oliveira, Caroline Torres de (2018)
The use of agroindustrial by-products is an interesting alternative for the production of cutinase by solid-state fermentation from a low cost process for viable industrial application of this enzyme. For this purpose, the production was evaluated using different substrates and fungal species of genera Fusarium. After the choice of the microorganism and the main substrate, process variables were studied aiming the maximization of cutinase production. A strategy was presented to maximize cutinase production by solid-state fermentation of different microorganisms and substrates. The best results were observed using Fusarium verticillioides, rice bran being the main substrate. The maximum cutinase production was 16.22 U / g at 28 ° C, 50% moisture content by weight, 2.5% by weight corn steep liquor, 2.5% by weight soybean meal and 15% by weight of inoculum after 10 days of fermentation. This enzyme was then subjected to concentration by means of a precipitation process using ethanol as the precipitating agent. The use of this agent is considered economically feasible and may be an alternative to obtain a more affordable end product. The assays that obtained better results were those with lower concentration of ethanol (10 %), reaching a concentration factor of 2.4. The concentrated enzyme presented optimum activity at pH and temperature of 35 ° C and pH 6.5, respectively. Stability was higher at lower temperatures (20 and 30 °C) and especially at storage temperature (5 °C). When subjected to temperatures of 40, 50 and 60 ° C, activity was lost more rapidly. Regarding the cutinase reaction pH was stable over the entire pH range tested (5 to 8) at a temperature of 30 °C.